"Your side of the street": Cormac McCarthy's collaborative authorship - King, Daniel Robert (2013)
In this thesis I investigate the relationship between contemporary author Cormac McCarthy and his editors: Albert Erskine at Random House and Gary Fisketjon and Dan Frank at Alfred A Knopf. In investigating these relationships I attempt to give insight into the working practices of McCarthy, and by doing so examine the changing world of publishing at Random House. I also explore the implications for established critical understandings of McCarthy's work of the significant changes which were made during the re-writing and editing of McCarthy's novels. In mapping relationships between author, editor and agent I conduct a study of the changing modes and models of author-editor and author-editor-agent relationships within Random House and its subsidiary Alfred A Knopf. Taking each of McCarthy's novels in turn as a case study I construct an examination of the relationships between this tightly knit core group and the various specialist collaborators who appear at scattered but significant moments during McCarthy's literary career. It is in this web of collaboration and interdependence in concert with established understandings of the author-role and author-function that this thesis builds its understanding of McCarthy's authorship practices.